Prof. Dr. K. Gülbün Baydur’a armağan - Esin Sultan Oğuz (Türk Kütüphaneciliği)
This study introduces some articles, interviews and remembrances for retirement of Prof. K. Gülbün Baydur who is member of Hacettepe University Department of Information Management.